ASUHAN KEBIDANAN PADA IBU BERSALIN NY S DENGAN DIDAMPINGI SUAMI GUNA PENGURANGAN RASA CEMAS MENGHADAPI PROSES PERSALINAN DI PUSKESMAS TANJUNG BALAI KARIMUN - Dwi Handayani, Pratiwi; Aryaneta, Yenni; Aidina, Dyka (Universitas Batam, 2024)
One of the hardest experiences for a mother is childbirth, because giving birth is one of the stakes for the life and death of a mother. Husband support during childbirth is a source of strength for mothers that cannot be provided by health workers. Objective To provide comprehensive and continuous midwifery care for mothers giving birth, with management of midwifery care in accordance with midwifery service standards. The midwifery care that was implemented was Midwifery Care for Mrs. S in Birth Accompanied by Her Husband to Reduce Anxiety in Facing the Childbirth Process. The practice report preparation method is descriptive research with the case study method conducted at the Tanjung Balai Karimun Health Center in March 2023. The subjects used in the case study with midwifery care management is Mrs. S. Results and Conclusions Evaluation of the care provided related to Midwifery Care for Mothers in Birth Mrs. S Accompanied by Her Husband to Reduce Anxiety Facing the Childbirth Process there is a reduction in the anxiety that mothers feel